Pengaruh Kualitas Pelayanan, Kualitas Produk Dan Harga Produk Terhadap Kepuasan Pelanggan Pada Nice So Kota Malang - Sejati, Eling Rosa; Sunaryo, Hadi; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of service quality, product quality and product price on Nice So customer satisfaction in the city of Malang. In the current era, there are many types of businesses that carry out various kinds of innovations based on customer needs. An example of a form of business that is widely known to the public is Nice So. It is a supermarket that provides products for daily needs, one of which is accessories, fashion equipment, office stationery and electronic equipment. The research method used was quantitative. Sampling used non-probability sampling with purposive sampling technique totaling 87 respondents. Data analysis uses multiple linear regression analysis. The results of this research show that simultaneously service quality, product quality and product price have a significant effect on customer satisfaction. Partially, product quality has a significant effect on customer satisfaction and product price has a significant effect on customer satisfaction. However, this research proves that service quality does not have a significant effect on customer satisfaction. Keywords: Customer Satisfaction, Service Quality, Product Quality, Product Price, Nice So